INCOME FLUCTUATIONS OF GRAIN INDUSTRIAL ENTREPRENEURIAL CANCER - Yumaajav Byambaarai, Enkhchimeg Dolgorsuren (International Journal of Modern Agriculture, 2021)
10 percent of the agricultural sector is made up of farming and 90 percent is made up of the livestock industry. Meat and meat products account for 12 percent of Mongolia’s food consumption, and flour and bakery products for 18 percent. This research aims to determine the current situation and perspective of the wheat industry, the main raw material of flour products, the main food of Mongolians. The size of the organization has a significant impact on the income volatility of wheat producers. Therefore, in order to ensure the income stability of businesses, the government needs to take measures such as capitalization, diversification of income from the implementation of crop rotation technologies, and the establishment of a joint technology park.